The Effect of Think Pair Share on the Students’ in Reading Comprehension - David Gultom; Anni Holila Pulungan (Universitas Negeri Medan, 2013)
This study was conducted as an attempt to discover the effect of Think Pair Share technique on Grade VIII students’ reading comprehension. It was an experimental research. The population of this study were the students of SMP Negeri 5 Medan, which consisted of 60 students. The research is divided into two groups: experimental and control groups. The instrument used to collect the data was reading comprehension test. To obtain the reliability of the test, the writer applied SPSS 17. From the result, it can be concluded that the experimental group’ score in posttest (M=54.33, SE=1.511). The paired sample correlation shows that the correlation is 0. 662. It means that it had strong correlation between pre-test and posttest in the experimental group. The calculation on effect size should be performed to find out how successful the treatment and how significant the improvement was and the findings indicated that using Think Pair Share significantly affected the students’ reading comprehension. So, English teachers were suggested to apply Think Pair Share in order to improve students’ reading comprehension.